Hematological Changes and Anemia Patterns Among Pregnant Women in Iraq: Perubahan Hematologi dan Pola Anemia pada Ibu Hamil di Irak - Fadhil, Safa Abd Alhadi (Academia Open, 2025)
Background: Anemia remains a critical global public health issue, significantly contributing to maternal morbidity and mortality, particularly in low-resource settings. Specific Background: In Iraq, the burden of anemia among pregnant women remains underexplored, with limited data on hematological profiles across trimesters. Knowledge Gap: Despite existing literature on anemia in pregnancy, there is a paucity of localized studies assessing its prevalence, severity, and potential causes beyond iron deficiency. Aim: This study aimed to determine the prevalence and severity of anemia among pregnant women attending Al-Alawiya Maternity Hospital in Baghdad, Iraq, and to evaluate associated hematological parameters. Results: A cross-sectional analysis of 110 pregnant and 50 non-pregnant women revealed a statistically significant decrease in hemoglobin and packed cell volume (PCV) among pregnant participants, particularly during the second and third trimesters and within the 26–40-year age group. Ferritin levels remained within normal limits across all groups. Novelty: The study highlights a modest prevalence of anemia not directly linked to iron deficiency, suggesting alternative etiologies such as micronutrient deficiencies or physiological changes during pregnancy. Implications: Routine monitoring of hematological parameters is essential, and further investigation is needed to identify non-iron-related causes of anemia in pregnancy to guide more effective interventions. Highlights: Hemoglobin drops in 2nd and 3rd pregnancy trimesters. Anemia most common in women aged 26–40. Ferritin normal—non-iron deficiency anemia suspected. Keywords: Anemia, Pregnancy, Hemoglobin, Ferritin, Iraq